Hemorrhage Risk Assessment on Admission: Utility for Prediction of Maternal Morbidity - Ahmadzia, Homa K.; Phillips, Jaclyn M.; Kleiman, Rose; Gimovsky, Alexis C.; Bathgate, Susan; Luban, Naomi L.C.; Amdur, Richard L. (American Journal of Perinatology, 2020)
Objective Hemorrhage is a major cause of maternal morbidity and mortality prompting creation of innovative risk assessment tools to identify patients at highest risk. We aimed to investigate the association of hemorrhage risk assessment with maternal morbidity and to evaluate maternal outcomes after implementation of the risk assessment across hospital sites.Study Design We conducted a retrospective cohort analysis of a multicenter database including women admitted to labor and delivery from January 2015 to June 2018. The Association of Women's Health, Obstetric and Neonatal Nurses risk assessment tool was used to categorize patients as low, medium, or high risk for hemorrhage. Multivariate logistic regression was used to describe the association between hemorrhage risk score and markers of maternal morbidity and evaluate maternal outcomes before and after standardized implementations of the risk assessment tool.Results In this study, 14,861 women were categorized as low risk (26%), 26,080 (46%) moderate risk, and 15,730 (28%) high risk (N = 56,671 births). For women with high-risk scores, the relative risk (RR) ratio compared with low-risk women was 4.9 (RR: 95% confidence interval [CI]: 3.2–7.4) for blood transfusion and 5.2 (RR: 95% CI: 4.6–5.9) for estimated blood loss (EBL) ≥ 1,000 mL. For the second objective, 110,633 women were available for pre- and postimplementation analyses (39,027 and 71,606, respectively). A 20% reduction in rates of blood transfusion (0.5–0.4%, p = 0.02) and EBL ≥ 1,000 mL (6.3–5.9%, p = 0.014) was observed between pre- and postimplementations of the admission hemorrhage risk assessment tool.Conclusion Women who were deemed high risk for hemorrhage using a hemorrhage risk assessment tool had five times higher risk for blood transfusion and EBL ≥ 1,000 mL compared with low-risk women. Given the low incidence of the outcomes explored, the hemorrhage risk assessment works moderately well to identify patients at risk for peripartum morbidity.Key Points
Keywords: hemorrhage risk assessment; maternal morbidity; obstetric hemorrhage; transfusion